Synchronizing eye tracking and optical motion capture: How to bring them together - Birgitta Burger; Anna Puupponen; Tommi Jantunen (Bern Open Publishing, 2018)
Both eye tracking and motion capture technologies are nowadays frequently used in human sciences, although both technologies are usually used separately. However, measuring both eye and body movements simultaneously would offer great potential for investigating cross- modal interaction in human (e.g. music and language-related) behavior. Here we combined an Ergoneers Dikablis head mounted eye tracker with a Qualisys Oqus optical motion cap- ture system. In order to synchronize the recordings of both devices, we developed a gener- alizable solution that does not rely on any (cost-intensive) ready-made / company-provided synchronization solution. At the beginning of each recording, the participant nods quickly while fixing on a target while keeping the eyes open - a motion yielding a sharp vertical displacement in both mocap and eye data. This displacement can be reliably detected with a peak-picking algorithm and used for accurately aligning the mocap and eye data. This method produces accurate synchronization results in the case of clean data and therefore provides an attractive alternative to costly plug-ins, as well as a solution in case ready-made synchronization solutions are unavailable.